Develop a New Lightweight Consensus Algorithm for IoT - Mahmood, Mahmood S.; Dabagh, Najla Badie AI (Technium Social Sciences Journal, 2022)
Blockchain has gained a lot of attention in non-financial applications like the Internet of Things (IoT). It is characterized by security, decentralization, anonymity, and auditability. Today's technology makes extensive use of the internet of things to gather data from sensors and carry out specific tasks by processing it according to the requirements. To produce secure and impermeable records of transactions, the collected data can be transferred through the blockchain network. The integration of blockchain with IoT has enormous promise due to its ability to offer decentralized computing, storage, and exchange for IoT data. Conventional blockchains generally have low throughput, long transaction delays, and rely on computationally expensive consensus algorithms. However, because of its limitations, IoT applications need a blockchain network that has a lightweight consensus algorithm to integrate with it successfully. In this paper, we implement and design a Lightweight Practical Byzantine Fault Tolerance (LPBFT) consensus algorithm that improves the conventional (PBFT) algorithm. Through the implementation of the proposed LPBFT, it has shown: a simpler message structure; doesn't need a primary server; low computation time; and consists of just two stages (request and reply). That makes it workable efficiently in IoT networks.